Effects of creation of bladder flap during cesarean section on long-term residual urine volume and postoperative urinary retention - Kanza Gül, Derya; Şolt, Ayça (Journal of Surgery and Medicine, 2020)
Aim: Postpartum urinary retention (PUR) is an important clinical condition that is frequently detected after both vaginal and cesarean delivery. The aim of this study was to evaluate PUR in women who did and did not have bladder flaps created during cesarean section and the effect of Kegel exercises on long-term bladder muscle function in those with high postnatal residual urine volume. Methods: This prospective randomized study was conducted with 100 primiparous pregnant women who were to undergo elective cesarean section between April and December 2019. Patients were divided into two groups: The experimental group (bladder flap group, n=50) and the control group (non-bladder flap group, n=50). The study data were collected with the Maternal Information Form and UDI-6. Kegel exercise results, post-void residual volume and urinary system symptoms were assessed on the 2nd and 5th postoperative day and 6 weeks after birth. Results: There were no significant differences between the groups in terms of socio-demographic characteristics, postoperative 5th day and 6th week residual urine volume, postoperative urinary retention volume, urinary system symptoms (UDI-6 scores) and bladder injury. There were significant differences between the groups in terms of residual urine volume, duration of surgery, and pain values assessed on the second day (P=0.045, P<0.001, P<0.001, respectively). Intra group comparisons demonstrated a decrease in residual urine volume in the participants with high residual urine volume after Kegel exercises, and their postoperative 2nd day and 6th week residual urine volumes and UDI-6 scores were significantly different (P<0.001, P<0.001). Conclusion: The present study determined that bladder flaps created during cesarean section increases postoperative urinary retention. In patients with high residual urine volume, Kegel exercises reduce residual urine volumes and urinary symptoms in the long term.